SAÚDE BUCAL E GESTAÇÃO EM UM CONTEXTO EDUCACIONAL: DIRETRIZES PARA AÇÕES EDUCATIVAS Santa Maria 2017 - Berlt, Maiara (2017)
take into account that the poor state of oral health of the mother can interfere in the health of the babies, already in the intrauterine condition. This can occur due to caries contamination and periodontal diseases during pregnancy. Nursing care is surrounded by beliefs, many of them advocating inappropriate behaviors for women, or stimulating their removal from dental offices and, therefore, from the examinations common to prenatal dentistry, which consists of caring for and educating pregnant women, so that she has her baby in general and oral health. This work consists of two articles and an end product, the first one entitled "Education and autonomy in self-promotion of oral health of pregnant women", and it is a review of non-systematic literature that evaluated the evidence of the importance of education and of autonomy in self-promotion of oral health of women, demonstrating that education should be used as a health strategy. The second article entitled "Oral care in gestation: perspectives of student mothers: preliminary note is a quantitative exploratory study and sought to investigate the level of information on oral health in gestation of mothers who study in a federal institution of high school, technical and superior in the interior of Rio Grande do Sul, concluding that a high percentage of women did not even hear about prenatal dentistry, even though they had already undergone maternity experience. Finally, we present a set of guidelines for an educational strategy aimed at developing the self-promotion capacity of oral health of pregnant women, which is the final product of this dissertation. The authors suggest that the practice of education in oral health results in the formation of critical awareness, and induces the materialization of actions and oral health care, by pregnant women. With the development of their autonomy mediated, they enjoy the freedom and the ability to choose care and seek care, a decision that influences their quality of life and the healthy development of their babies.